Phenotypic screen identifies calcineurin-sparing FK506 analogs as BMP potentiators for treatment of acute kidney injury. Issue 9 (16th September 2021) - Larraufie, Marie-Hélène; Gao, Xiaolin; Xia, Xiaobo; Devine, Patrick J.; Kallen, Joerg; Liu, Dong; Michaud, Gregory; Harsch, Andreas; Savage, Nik; Ding, Jian; Tan, Kian; Mihalic, Manuel; et al.
Summary: Acute kidney injury (AKI) is a life-threatening disease with no known curative or preventive therapies. Data from multiple animal models and human studies have linked dysregulation of bone morphogenetic protein (BMP) signaling to AKI. Small molecules that potentiate endogenous BMP signaling should have a beneficial effect in AKI. We performed a high-throughput phenotypic screen and identified a series of FK506 analogs that act as potent BMP potentiators by sequestering FKBP12 from BMP type I receptors. We further showed that calcineurin inhibition was not required for this activity. We identified a calcineurin-sparing FK506 analog oxtFK through late-stage functionalization and structure-guided design. OxtFK demonstrated an improved safety profile in vivo relative to FK506. OxtFK stimulated BMP signaling in vitro and in vivo and protected the kidneys in an AKI mouse model, making it a promising candidate for future development as a first-in-class therapeutic for diseases with dysregulated BMP signaling. Graphical abstract: Highlights: Phenotypic screen identifies FK506 as BMP potentiator sequestering FKBP12 from BMPRI Calcineurin inhibition is not required for BMP potentiation Calcineurin-sparing FK506 analogs identified via late-stage functionalization OxtFK preserves renal functions in vitro and in vivo with high safety margins Abstract : Larraufie and Gao et al. determine that FK506 analogs can potentiate BMP signaling by inhibiting the interaction of BMP receptors with FKBP12. Using structure-based design, they identify a novel calcineurin-sparing analog, oxtFK, that preserves renal function in vitro and in vivo with improved safety margins compared with FK506.